Performance of digital radiography with enhancement filters for the diagnosis of proximal caries - Belém,Manuella Dias Furtado (2013)
Enhancement filters are potentially supposed to improve the diagnostic performance of digital images. Thus, the aim of this study was to compare the performance of digital radiography with and without enhancement filters for the detection of induced proximal caries lesions. The total sample consisted of 120 sound human teeth (40 premolars, 80 molars). Enamel subsurface demineralization was induced in one of the proximal surfaces of 60 teeth. Standardized radiographs of all teeth were acquired after the demineralization phase using the Digora-Optime® system. Four radiologists examined the digital radiographs and applied the following filters provided by the Digora® for Windows 2.6 package: Negative, Sharpen and both (Negative plus Sharpen). Validation of radiographic diagnosis was carried out by Knoop cross-sectional micro-hardness profiling on the proximal surfaces. Intraobserver agreement was estimated using Kappa statistics (k). Sensitivity, specificity and over-all accuracy were compared using ANOVA/Tukey test (α = 5%). Intraobserver agreement ranged from good to very good/optimal (k: 0.65–0.83). Although not statistically significant, the highest sensitivity (0.68 ± 0.22) and accuracy (0.76 ± 0.16) values were observed using the Sharpen filter as opposed to the Negative filter, which presented the lowest performance indices (0.57 ± 0.13 and 0.70 ± 0.10, respectively). Specificity ranged from 0.84 to 0.85, considering all imaging modalities (p > 0.05). Insofar as the Sharpen filter had the highest performance indices, it may be considered a useful adjunct for detecting subtle proximal caries lesions.